Evaluation of children with ventricular arrhythmias. Issue 5 (May 1977) - Radford, D J; Izukawa, T; Rowe, R D
Abstract : Ventricular arrhythmias are rare in childhood but may be associated with syncope and sudden death. This report describes 8 children with ventricular arrhythmias, 6 of whom suffered syncopal episodes. Ventricular tachycardia was documented in 5. One boy died suddenly. Complete cardiac investigation was carried out with exercise testing, Holter monitoring, echocardiography, cardiac catheterization, angiography, and electrophysiological studies. The spectrum of abnormalities related to the arrhythmias included prolapsing mitral valve, prolonged QT syndrome, sick sinus syndrome, congenital heart disease, cardiomyopathy, and idiopathic ventricular tachycardia. Exercise testing and Holter monitoring were particularly useful in documenting the arrhythmias and monitoring response to therapy.